Attitűd és értésmód: egy irodalmi korszakváltás alapfogalmai: Borbély Szilárd irodalomtörténeti koncepciójáról - S. Varga, Pál (Studia Litteraria, 2016)
Szilárd Borbély described the periodical change in poetry at the turn of the 18th and 19th century as a ”shift in the attitude of literary texts” and as a transformation of ”literary understanding”. The turning away from the late Baroque and Classic poetry – which both followed inherited models of genre – came when the narrator received a unique identity, and the reader began to understand the text as an expression of the Self. This change can be pointed out in Sándor Kisfaludy’s cycle of poems, Kesergő szerelem (1802), which influenced the creation of Csokonai’s own cycle of love poems. The temporalization of the attitude towards the textual genre happened in the poetry of Ferenc Kölcsey. The narrators of Kölcsey’s Vanitatum vanitas and Hymnus create their identity by uniquely reflecting on the genre and dislocating the ready-made meanings. The peak of the transition is the inventive formation of history by means of poetry and language. The epic poetry of Mihály Vörösmarty structures language in a way that makes the mythical recounting of origin possible for the subject attempting to establish an identity in the past. Yet this language brought about the paradox of excluding the subjective from the expression. The concept emphasizing the formation of the attitude that reflects on the genre by language is not only a re-interpretation of 18th-19th century Hungarian poetry, but it is obviously close to the postmodern poetic method which is attributed to Halotti pompa [The Splendours of Death].